2018
DOI: 10.1080/10641955.2017.1411946
|View full text |Cite
|
Sign up to set email alerts
|

Early pregnancy protein multiplex screening reflects circulating and urinary divergences associated with the development of preeclampsia

Abstract: The proteins sEGFR, HGF, ANG-2, sFASL, IL-6, PLGF, VEGF-A, PRL, TGF-α FGF-b, sHER2/Neu sIL-6Rα, ENG, uPA, and insulin-like growth factor binding protein 1 (IGFBP-1), were predictive of the development of preeclampsia and their use as markers for this disease should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…However, due to the disturbed endothelial cell function in placental tissue in severe PE cases, the regulation of this imbalance may be not possible and it may explain the lower FGF2 serum concentrations observed in women with severe PE Hohlagschwandtner et al, 2002). The relationship between the circulating FGF2 concentration and PE development has been reported in other studies, in which a decrease in FGF2 plasma concentrations was observed at 16 WG in pregnant women who subsequently developed PE when they were compared with women with normotensive pregnancies (Martinez-Fierro et al, 2015;Martinez-Fierro et al, 2018b). Based on the above, we inferred that low FGF2 circulating concentrations could be due to the poor response of the FGF2 regulatory mechanism.…”
Section: Introductionsupporting
confidence: 82%
“…However, due to the disturbed endothelial cell function in placental tissue in severe PE cases, the regulation of this imbalance may be not possible and it may explain the lower FGF2 serum concentrations observed in women with severe PE Hohlagschwandtner et al, 2002). The relationship between the circulating FGF2 concentration and PE development has been reported in other studies, in which a decrease in FGF2 plasma concentrations was observed at 16 WG in pregnant women who subsequently developed PE when they were compared with women with normotensive pregnancies (Martinez-Fierro et al, 2015;Martinez-Fierro et al, 2018b). Based on the above, we inferred that low FGF2 circulating concentrations could be due to the poor response of the FGF2 regulatory mechanism.…”
Section: Introductionsupporting
confidence: 82%
“…This was a retrospective nested cohort case-control study in which the participants were drawn from a cohort of pregnant women who were followed from the first trimester to delivery as part of a screening study for adverse pregnancy outcomes, in Zacatecas Mexico [ 20 , 21 ] ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…This was a retrospective nested cohort case-control study in which the participants were drawn from a cohort of pregnant women who were followed from the first trimester to delivery as part of a screening study for adverse pregnancy outcomes, in Zacatecas Mexico [20,21] (Figure 1). which quantified miRNA profiles in first-trimester serum samples from pregnant women who subsequently developed early PE, significant miRNA signatures were not identified [13].…”
Section: Patients and Study Designmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the role of the family history of hypertension as an independent risk factor of pregnancy-induced hypertension (PIH) has not been clearly established [ 4 , 8 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Only the Society of Obstetricians and Gynaecologists of Canada (SOGC) 2014 guidelines list a family history of early cardiovascular disease among the risk factors for preeclampsia (PE) that determine the use of aspirin prophylaxis, in contrast to the guidelines of other scientific societies [ 11 ].…”
Section: Introductionmentioning
confidence: 99%